A Proposal of an Integral Evaluation within the Teaching English Major in the Faculty of Literature, Language and Science in the National University of Costa Rica - Guzmán Arce, Natin Gerardo; Loaiza Berrocal, Mayra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
It is the main objective of this proposal to carry out a coordination of an Integral Evaluation within all the subjects taught in the Teaching English Major provided by the Faculty of Literature, Language and Science in the National University of Costa Rica. This proposal aims to involve all parties: faculty members, professors and students in order to obtain much better results in the learning process of the English Language. This Integral Evaluation procedure intends to help students see the learning of the language as a whole contemplating oral, written, spoken and listening and comprehension production as a unique element as well as a result throughout the different tasks (projects) given to students based on the topics and course objectives. The main goal is to establish this proposal as a regular activity in the major depending on the different major levels.